ORIGINS OF THE COSSACK ERA AND INFLUENCE ON FOLK PROSE - Nataliia Rudakova (Taras Shevchenko National University of Kyiv, 2021)
The article considers the particular influence of dynamic and integrity of the historical process in the Cossack's prose tradition. It inherited not only the semantic and formal stereotypes of the squad epic, but also peculiar outlook and original metaphysics that outlined the position of human beings in the world, and the philosophical morality of the ancient period, adapted to the specific reality of the Cossack era. The natural connections of Cossack's prose with public life, ethnic traditions, and material culture determined the necessity to study as an important source for ascertainment the processes of existence and development of the Cossack epic system. It was also analyzed what historical circumstances brought the appearance in prose of homesickness, longing for family, native land, as well as tragic rupture of family ties into the prose of a permanent motive. The Cossacks in Ukraine appeared together with the colonization of the marginal lands, which were a part of the Lithuanian-Polish state. It has been found that the structure of many prose samples naturally includes toponymic motives based on folk etymology, which give the works a notable "historical" authenticity. It was found that in the period of formation, the Cossacks were not a military organization, it was a kind of household phenomenon or craft. In this sense, the Cossacks have been known since ancient times, but the term appeared in the late 15th century and they were transformed into a social stratum during the 12th century. According to our analysis, the main premise for the prose tradition of the Cossacks background were historical factors that have created the great national movement within the current Cherkasy region that involved the bulk of the population of the Middle Dnieper in the 16th century. Different conditions of the historical being of the eastern and western regions influenced the centers of epic creativity, coinciding with the ethno-destriction of Ukraine.